PENGARUH SERTIFIKASI DAN SARANA PRASARANA TERHADAP PROFESIONALISME GURU SD NEGERI SE KECAMATAN SUAK TAPEH KABUPATEN BANYUASIN - Herlani Herlani; Tri Widayatsih; Suherman Suherman (STKIP Pesisir Selatan, 2026)
infrastructure on the teachers performance of the state elementary school in Suak Tapeh District of Banyuasin Regency, both partially and simultaneously. The sample of this study was 69 elementary school teachers in Suak Tapeh District of Banyuasin Regency. The method used was a quantitative method with an expo pacto approach. The data collection techniques used questionnaires and documentation. The research of the data analysis technique used the SPSS program. The results of this study concluded: 1) there is an influence of certification on the teachers performance of the state elementary school in Suak Tapeh District ofBanyuasin Regency; 2) there is an influence of infrastructure on the teachers performance of the state elementary school in Suak Tapeh District of Banyuasin Regency; 3) there is an influence of certification and infrastructure simultaneously on the teachers performance of the state elementary school in Suak Tapeh District of Banyuasin Regency.